Nasze naymilsze siestrzyczki... czyli habitki w klasztorze Wizytek Warszawskich w XVII wieku - Szylar, Anna (Biuletyn Historii Wychowania, 2010)
The sisters of the Order of the Visitation of Holy Mary, more commonly known as Visitationists, were brought to Poland from France by Marie Louise Gonzaga (known in Poland as Ludwika Maria) in 1654. Visitationists ran a boarding school for girls and provided education for inner-city girls from less well-to-do backgrounds. In addition, the religious order for women accommodated a novitiate for young girls admitted to this religious order for women – the so-called habitki (from the habit of a member under vows), i.e. candidates for the convent. The present article provides the reader with some detailed information on the mentioned group of candidates in relation the period covering the years from the establishment of the convent to the end of the seventeenth century. Habitki’s cells were located in the part of the convent that also accommodated nuns, wore habits and participated in regular religious services and prayers with nuns. As a rule, they were usually minors up to girls of several years of age or older. They were supervised by a master-nun, appointed by Mother Superior, who took care of them, while a special rule of conduct determined their duties and responsibilities in the convent. The reasons behind a decision to send little girls to the nunnery varied. At times, still unborn babies were sacrificed to God even before delivery, a custom to be found in particular within families where children were long in coming or where successive deliveries were death experiences for parents. Girls in the convent usually had both parents, but oftentimes they were orphans, disabled, hated by their parents or came from large families. By sending a daughter to a convent parents believed that her future was somehow secured. Occasionally, by doing so they simply got rid of a crippled child that often required extra care, or cleared the situation in prospective property settlement agreements in the family. More often than not, the plans conceived by parents, or foster parents, were not in line with intentions or expectations of girls. A decision to stay within the confinement of the convent, however, was up to a candidate, who, after reaching the age of 15, was entitled to seek for admittance to the full novitiate and, at the age of 16, could take simple vows. Between 1658 and 1697, the Warsaw-based convent had 23 habitki. Only 7 of them took vows. At the time, no other religious order and convent had such a specific rule for child.